Chromium-free carbon-free complex-phase corundum stuffing sand for smelting variety steel and preparation method of chromium-free carbon-free complex-phase corundum stuffing sand

By developing chromium-free and carbon-free composite corundum drainage sand, using silicon sol impregnation coating treatment and aluminum-silicon modifier coating technology, the existing drainage sand has been solved and the problems of low self-opening rate and affecting the quality of molten steel are achieved, and the efficient isolation layer formation and the self-opening rate of high-value-added steels have been improved.

CN119822798APending Publication Date: 2025-04-15ZHEJIANG ZILI HIGH TEMPERATURE TECH CO LTD +1

Patent Information

Application Number
CN202510154282.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing drainage sand has a low self-opening rate in ladle smelting, which affects continuous casting production efficiency and casting quality, and contains chromium and carbon, affecting the quality of molten steel.

Method used

A chromium-free and carbon-free complex corundum drainage sand was developed, and it was coated with silicon sol impregnation coating and aluminum-silicon modifier to form an efficient isolation layer, improving self-opening rate and anti-permeability.

Benefits of technology

It realizes the rapid formation of a dense isolation layer at the water outlet of the refined ladle, prevents penetration and erosion of liquid steel/slag, improves the self-casting rate of high-value-added steel, reduces the boiling oxygen pouring and continuous casting breaking, and ensures the efficient forward and steel casting quality of continuous casting production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005269082180000031
    Figure BDA0005269082180000031
  • Figure BDA0005269082180000091
    Figure BDA0005269082180000091
  • Figure BDA0005269082180000101
    Figure BDA0005269082180000101
Patent Text Reader

Abstract

The invention discloses chromium-free and carbon-free complex-phase corundum stuffing sand for smelting variety steel and a preparation method of the chromium-free and carbon-free complex-phase corundum stuffing sand. The stuffing sand is prepared from the following raw materials in parts by mass: 60 to 90 parts of complex phase corundum subjected to silica sol dipping and coating treatment, 5 to 30 parts of zircon sand, 0.5 to 10 parts of sintering aid, 0.5 to 2 parts of silica sol and 1.5 to 5 parts of aluminum-silicon modifier. The preparation method comprises the following steps: uniformly mixing the multiphase corundum subjected to silica sol dipping and coating treatment, the zircon sand and the sintering aid, adding the silica sol, uniformly mixing, adding the aluminum-silicon modifier, uniformly mixing, drying at 150-250 DEG C, removing false particles, and screening to obtain the stuffing sand. The ladle filler sand is suitable for smelting of special varieties of steel, a compact isolation layer can be rapidly formed on the hot surface of a nozzle part of a refined steel ladle, permeation and erosion of molten steel / slag are effectively prevented, the self-casting rate of the refined steel ladle of the variety of steel with high added value is increased, oxygen burning casting is reduced, continuous casting broken casting is reduced, efficient and smooth continuous casting production is guaranteed, and the quality of a steel casting blank is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of grade steel smelting, and in particular to a chromium-free and carbon-free complex phase corundum drainage sand for grade steel smelting and a preparation method thereof. Background Art

[0002] With the increasing demand for high-grade steel, especially the sharp increase in demand for ultra-low carbon steel, clean steel, aluminum-killed steel and silicon steel, the impurity content in molten steel is required to be as low as possible, which requires refractory materials not to affect the quality of molten steel. In steelmaking production, drainage sand is used to plug the drainage at the injection hole at the bottom of the ladle, and is an indispensable refractory material for the ladle. The automatic pouring rate of the ladle is a key indicator that determines the smooth flow of continuous casting production. If the molten steel cannot flow out automatically after opening the slide, oxygen drainage must be adopted. The adverse consequences are that it directly affects the production efficiency of the continuous casting process, the quality of the ingot and causes safety hazards. In the actual production process, the drainage sand commonly used in the smelting of refined ladle is still mainly chromium drainage sand, and there is a small amount of zirconium drainage sand. Both types of drainage sand use a small amount of graphite / carbon black as a reducing agent and wetting agent.

[0003] After searching, Chinese patent CN101972847B relates to a chromium drainage sand for special steel and its preparation process, which includes: 62wt%~70wt% chromite, 28wt%~33wt% quartz sand, 1wt%~1.5wt% graphite powder, and 0.5wt%~1.5wt% phenolic resin as a binder, with a self-opening rate ≥90%.

[0004] Chinese patent CN104148625B relates to a method for preparing refined chromium drainage sand, comprising: 60wt% to 65wt% chromium ore sand, 25wt% to 33wt% quartz sand, 4wt% to 7wt% potassium feldspar, 2wt% to 3wt% low-grade silicon carbide and 1wt% to 2wt% carbon black.

[0005] Chinese patent CN103708842B relates to a chromium-magnesium-zirconium drainage sand and a preparation method thereof, comprising: Cr2O3=36±3wt%, MgO=14±2wt%, Al2O3=16±2wt%, SiO2=11±2wt%, Fe2O3=16±2wt%, ZrO2=4±2wt%, H2O<0.5wt%, and the rest is C; zirconium material is introduced, and a layer of zirconium oxide powder is coated on the surface of the drainage sand particles to improve the refractoriness of the drainage sand. Due to its high refractoriness, good thermal stability and strong anti-sintering ability, the purpose of increasing the pouring rate is achieved.

[0006] Chinese patent application CN112743071A relates to a high-Cr alloy steel drainage sand and a method for adding the same. A composite sand adding mode is adopted, wherein the upper layer adopts siliceous drainage sand, with SiO2≥75wt% and an added mass of 9 to 16kg / furnace; the lower layer adopts zirconium drainage sand, with Cr2O3=28wt% to 32wt%, SiO2=24wt% to 28%, and ZrO2=10wt% to 14wt%, and an added mass of 28 to 42kg / furnace.

[0007] Chinese patent application CN117326875A relates to a refined ladle zirconium drainage sand for high alloy steel and a preparation method thereof, comprising: 20.0wt% to 45.0wt% ZrO2, 25.0wt% to 35.0wt% SiO2, 10.0wt% to 15.0wt% Al2O3, 3.5wt% to 10.5w% MgO, 5.0wt% to 15.0wt% Cr2O3, 4.0wt% to 10.0wt% Fe2O3 and 0.5wt% to 1.5wt% total carbon (TC).

[0008] In order to ensure the self-opening rate of special steel smelting, the sintering performance and resistance to molten steel penetration are further optimized on the basis of conventional chromium drainage sand, by introducing SiC or wrapping a layer of zirconium oxide powder, or directly using low-zirconium drainage sand or zirconium drainage sand, but the above drainage sand still contains some Cr2O3 and C.

[0009] In order to meet the higher smelting requirements of special steel varieties for molten steel quality, the material of drainage sand tends to be chromium-free and carbon-free. After searching, Chinese patent CN104193353B relates to a plate-like corundum drainage sand and its preparation method, which contains 83-95 parts by weight of plate-like corundum sand, 0.5-10 parts by weight of magnesia sand, 0.2-5 parts by weight of graphite, 1-5 parts by weight of high-temperature sintering agent, and 0.2-2 parts by weight of low-temperature sintering agent, but the prepared corundum drainage sand still contains a small amount of graphite and boric acid, which limits its special steel smelting. Chinese patent applications CN110357644A and CN102000790A relate to a low-chromium environmentally friendly drainage sand and an aluminum environmentally friendly drainage sand and its production process and application, using high-aluminum casting sand (Al2O3≥76%) to partially replace or completely replace chromium ore sand. In actual application, it cannot directly contact molten steel and has a poor self-casting rate.

[0010] In summary, in order to meet the smelting needs of special types of steel, it is necessary to develop a special chromium-free and carbon-free drainage sand, improve and perfect the ladle drainage sand in the existing technology, and ensure the automatic pouring rate of the refining ladle without affecting the quality of the molten steel. Summary of the invention

[0011] In view of the above technical problems and the deficiencies in the art, the present invention provides a chromium-free and carbon-free complex phase corundum drainage sand for special steel smelting and a preparation method thereof. The drainage sand of the present invention is suitable for the smelting of special steel varieties, and can quickly form a dense isolation layer on the hot surface of the water inlet of the refining ladle, effectively prevent the penetration and erosion of molten steel / slag, improve the self-casting rate of the high value-added steel refining ladle, reduce oxygen burning for pouring, reduce continuous casting interruption, ensure efficient and smooth continuous casting production, and improve the quality of steel ingots.

[0012] [1] A type of chromium-free and carbon-free composite corundum drainage sand for steel smelting, the raw material composition of which, by weight, includes:

[0013]

[0014]

[0015] The preparation method of the complex phase corundum treated by silica sol impregnation and coating comprises: immersing the complex phase corundum raw material into a silica sol solution, and then placing it in a vacuum device for vacuum treatment, with a vacuum degree of less than 0.1 MPa, and maintaining the pressure for more than 2 hours, wherein the SiO2 content in the silica sol solution is 30wt% to 40wt%, taking out the treated complex phase corundum, and drying it at a low temperature of 150 to 250° C. (e.g., 200° C.), so as to obtain the complex phase corundum treated by silica sol impregnation and coating;

[0016] The sintering aid includes one or two of potassium feldspar and andalusite;

[0017] The raw material mass parts of the aluminum silicon modifier include:

[0018] 0.5-4 parts of alumina powder,

[0019] 0.5-3 parts of silicon oxide powder,

[0020] 0.5 to 1 part of aluminum silicon binder.

[0021] Based on the consideration of ensuring the self-opening rate of the high-grade steel refining ladle and not affecting the quality of molten steel, the present invention provides a chromium-free and carbon-free complex phase corundum drainage sand for grade steel smelting, which has the following characteristics: using complex phase corundum particles treated by silica sol impregnation and coating, coordinating with zircon sand and sintering aids in a specific dosage ratio, and then infiltrating with silica sol, and then coating the surface with aluminum silicon modifier. The chromium-free and carbon-free complex phase corundum drainage sand obtained in this way can quickly form a dense isolation layer on the hot surface of the water inlet of the refining ladle, effectively preventing the penetration and erosion of molten steel / slag, and the drainage sand material has excellent corrosion resistance and permeability, so that its sintering and permeation layers are thin, which is convenient for the static pressure of molten steel to easily break the sintering layer when the slide plate is opened, so as to achieve the purpose of self-opening. For the smelting of special grade steel, the present invention improves the self-opening rate of the high value-added grade steel refining ladle, reduces oxygen burning and pouring, reduces continuous casting interruption, ensures efficient and smooth continuous casting production, and improves the quality of steel ingots.

[0022] In some embodiments, the total mass of the chromium-free and carbon-free complex phase corundum drainage sand for smelting the described type of steel, the complex phase corundum treated with silica sol impregnation and coating, zircon sand, sintering aid, silica oxide sol and aluminum silicon modifier can be 100 parts.

[0023] In some preferred examples, the proportion of particles with a particle size of 0.088 to <1.0 mm in the chromium-free and carbon-free complex phase corundum drainage sand for smelting the above-mentioned type of steel is ≥90%, and more preferably >95%.

[0024] In some preferred examples, the moisture content of the chromium-free and carbon-free complex phase corundum drainage sand for smelting the above-mentioned type of steel is ≤0.3wt%, and more preferably ≤0.05wt%.

[0025] The bulk density of the chromium-free and carbon-free complex phase corundum drainage sand for steel smelting of the present invention is greater than 1.9g / cm 3 If the density is too small, the drainage sand particles will float up, which is not conducive to pouring.

[0026] The chromium-free and carbon-free complex phase corundum drainage sand for steel smelting of the present invention has an angle of repose of ≤18.5°, good particle fluidity and easy filling.

[0027] The self-opening rate of the chromium-free and carbon-free complex phase corundum drainage sand for smelting the steel of the present invention is greater than 96%.

[0028] In some preferred examples, the complex phase corundum raw material is one or both of fused Al2O3-rich spinel and sintered Al2O3-rich spinel, and the main phase is preferably 75wt% to 95wt% corundum phase and 5wt% to 25wt% aluminum-magnesium spinel eutectic. The present invention uses complex phase corundum aggregate, the main phase of which is corundum phase (75wt% to 95wt%) and aluminum-magnesium spinel (5wt% to 25wt%) eutectic. Compared with plate-like corundum aggregate, the introduction of part of the second phase defect magnesium-aluminum spinel phase into the aggregate can significantly improve the thermal shock resistance and erosion / permeability resistance of the aggregate.

[0029] In some embodiments, the Al2O3 content in the multiphase corundum raw material is ≥94.0wt%, the MgO content is 1wt% to 5wt%, and the Al2O3+MgO content is ≥98.5wt%.

[0030] In some preferred examples, the particle size distributions of the complex phase corundum raw material and the complex phase corundum treated by silica sol impregnation and coating can be independently as follows, calculated by weight:

[0031] 1~0.5mm, excluding 1mm 20~50 parts, for example 40 parts, etc.,

[0032] 0.5-0.15 mm, excluding 0.5 mm 20-70 parts, for example 27 parts, etc.

[0033] The use of the above-mentioned multiphase corundum raw material with the preferred particle size distribution can improve the sintering bonding between the particles and the coating material.

[0034] In some embodiments, in the method for preparing the complex phase corundum treated by silica sol impregnation and coating, low temperature drying and heat preservation at 150-250° C. are performed for 5-12 hours (eg, 8 hours, etc.).

[0035] In some preferred examples, the particle size of the zircon sand is 0.5-0.088 mm, excluding 0.5 mm.

[0036] In some embodiments, the zircon sand has a ZrO2 content of ≥60.0wt%, a SiO2 content of 25.0wt% to 40.0wt%, and a ZrO2+SiO2 content of ≥97.0wt%.

[0037] In the raw material composition of the chromium-free and carbon-free complex phase corundum drainage sand for smelting the above-mentioned steel, the sintering aid is preferably 3 to 5 parts by mass, and the obtained chromium-free and carbon-free complex phase corundum drainage sand for smelting the above-mentioned steel has lower high-temperature compressive strength and thinner sintered layer thickness.

[0038] The sintering aid preferably includes potassium feldspar and andalusite. Potassium feldspar and andalusite are used as composite sintering aids. Potassium feldspar forms a liquid phase at 1200-1300°C, while andalusite decomposes at 1400-1500°C to form mullite and a low-melting phase. The two promote sintering at different temperatures, which improves the sintering property of the drainage sand under different temperature gradients. In some preferred examples, in the sintering aid, the mass ratio of the andalusite to the potassium feldspar is 1:1.5-8, for example, 1:2.

[0039] In some preferred examples, the particle size of the potassium feldspar is 1.0 to 0.15 mm, excluding 1 mm.

[0040] In some embodiments, the potassium feldspar has a K2O content of 2.0wt% to 25.0wt%, a Na2O content of 2.0wt% to 20.0wt%, and a SiO2 content of ≥60.0wt%.

[0041] In some preferred examples, the particle size of the andalusite is 1.0 to 0.15 mm, excluding 1 mm.

[0042] In some embodiments, the andalusite has an Al2O3 content of 50.0wt% to 60.0wt%, a SiO2 content of 40.0wt% to 50.0wt%, and a K2O+Na2O content of ≤1.0wt%.

[0043] In some preferred examples, the particle size of the aluminum silicon modifier is ≤3 μm.

[0044] In some preferred examples, the particle size of the alumina powder is ≤4.0 μm.

[0045] In some embodiments, the Al2O3 content in the composition of the alumina fine powder is ≥ 99.0wt%.

[0046] In some preferred examples, the particle size of the silicon oxide powder is ≤2.0 μm.

[0047] In some embodiments, the SiO2 content in the composition of the silicon oxide powder is ≥ 95.0wt%.

[0048] In some preferred examples, the particle size of the aluminum-silicon binder is not greater than 5 μm.

[0049] In some preferred examples, the Al2O3+SiO2 content in the composition of the aluminum-silicon binder is ≥85.00wt%, and the 950°C ignition loss is ≤5.0wt%, so as to reduce the influence of low-melting-point phase impurities on the performance of drainage sand.

[0050] In some preferred examples, the preparation method of the aluminum silicon modifier comprises: grinding aluminum oxide powder, silicon oxide powder and aluminum silicon binder to obtain the aluminum silicon modifier. Further, the grinding can be ball milling. Further, the ball milling speed can be 100 to 300 rpm (e.g., 150 rpm, etc.), and the ball milling time can be 2.0 to 3.0 h (e.g., 2.5 h, etc.).

[0051] The specially prepared aluminum-silicon modifier is co-grinded to coat the complex phase corundum and zircon sand particles, strengthen the bonding between the particle aggregate and the micro powder, and can form micron-sized mullite rings in situ in the complex phase corundum and zircon sand particle coating layer at a relatively low temperature, resulting in a slight volume expansion and closed matrix pores, so that the drainage sand has excellent resistance to slag erosion and permeability; at the same time, during long-term service, under high temperature conditions, the sintering aid (potash feldspar and / or andalusite) forms a Na2O-K2O-Al2O3-SiO2 low-melting phase, which accelerates the SiO2 in some zircon sand particles to diffuse through the liquid phase and dissolve, forming mullite phase, low-melting phase and ZrO2 microcrystals in situ, and utilizing the ZrO2 dispersion toughening effect to improve its anti-erosion and permeability properties. On the other hand, after the ladle slide is opened, the unsintered drainage sand in the lower layer falls naturally, and the cold air enters the gap, lowering the temperature in the middle semi-sintered layer. The dispersed ZrO2 microcrystals undergo phase transformation toughening and form microcracks, making it easier for the static pressure of the molten steel to break the drainage sand sintered layer.

[0052] Alumina micropowder, silica micropowder and aluminum silicon binder in the raw materials of aluminum silicon modifier are co-grinded. On the one hand, the coating components are made more uniform, the coating effect is improved, and the abnormal performance of drainage sand particles caused by uneven components is prevented, resulting in local unevenness in the filling process, and abnormal oxygen burning or final pouring under the condition of differences in sintering and corrosion resistance / permeability; on the other hand, during the co-grinding process, the surface of the aluminum silicon modifier powder will react to generate micro-nano mullite phase nuclei, thereby greatly reducing the temperature of mullite phase formation (can be reduced by 50-100°C), enhancing the bonding strength between particles, promoting the sintering of drainage sand, and quickly forming a dense sintered layer at low temperature.

[0053] In some embodiments, the SiO2 content in the silica sol is 30wt% to 40wt%, the Na2O content is ≤0.7wt%, the SiO2 particle size in the silica sol is 5 to 25nm, and the pH value of the silica sol at 20°C is 8.5 to 10.5.

[0054] The chromium-free and carbon-free composite corundum drainage sand of the present invention preferably uses composite corundum of specific particle size and composition, zircon sand and sintering aid as main materials, uses silica sol as a wetting agent, and uses aluminum silicon modifier as a coating material, and further preferably optimizes the particle size, composition and preparation process of the aluminum silicon modifier, so that each component has a synergistic and synergistic effect. During the on-site application process, the chromium-free and carbon-free composite corundum drainage sand is filled into the water outlet through an artificial / sand guide pipe, and the filling height is 100 to 150 mm higher than the outlet seat brick to form a bulge. Due to its specific particle grading and coating structure, it can prevent particle segregation during packaging, transportation and filling, and ensure the uniformity of the composition of each particle of the drainage sand. When the drainage sand contacts the high-temperature molten steel, at the contact interface, due to the erosion and penetration of the temperature gradient and the high-temperature molten steel / slag, a dense sintering isolation layer is quickly formed on the hot surface of the drainage sand, which effectively prevents further penetration and erosion of the molten steel / slag.

[0055] [2] The method for preparing chromium-free and carbon-free complex phase corundum drainage sand for smelting the grade steel described in [1] comprises: firstly mixing the complex phase corundum impregnated and coated with silica sol, zircon sand and sintering aid evenly, then adding silica sol and mixing evenly, then adding aluminum silicon modifier and mixing evenly, low temperature drying at 150 to 250°C (e.g. 200°C, etc.), removing false particles after drying, and screening the product particles to obtain the chromium-free and carbon-free complex phase corundum drainage sand for smelting the grade steel described.

[0056] In some embodiments, in the method for preparing the chromium-free and carbon-free complex phase corundum drainage sand for smelting the type of steel, the sand is dried and kept warm at a low temperature of 150 to 250° C. for 5 to 12 hours (e.g., 8 hours, etc.).

[0057] The raw materials of the chromium-free and carbon-free complex phase corundum drainage sand of the present invention do not contain chromite, graphite / carbon black, phenolic resin, etc., and will not increase Cr2O3 and C, etc. in molten steel. Therefore, the prepared chromium-free and carbon-free complex phase corundum drainage sand is suitable for the smelting of special types of steel.

[0058] Compared with the prior art, the present invention has the following beneficial effects:

[0059] 1. The present invention uses aluminum-silicon binder and silicon oxide micropowder, aluminum oxide micropowder and other components to form a special aluminum-silicon modifier, and then uses silicon sol impregnation and coating to form chromium-free and carbon-free complex phase corundum drainage sand with complex phase corundum, zircon sand and sintering aid. The obtained chromium-free and carbon-free complex phase corundum drainage sand can quickly form a dense isolation layer on the hot surface of the water inlet of the refining ladle, effectively prevent the penetration and erosion of molten steel / slag, improve the self-casting rate of the high value-added steel refining ladle, reduce oxygen burning and pouring, reduce continuous casting interruption, ensure efficient and smooth continuous casting production, and improve the quality of steel ingots.

[0060] 2. The raw materials of chromium-free and carbon-free complex phase corundum drainage sand do not contain chromite, graphite / carbon black, phenolic resin, etc., and will not increase Cr2O3 and C in molten steel. It is suitable for the smelting of special types of steel. DETAILED DESCRIPTION

[0061] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples where no specific conditions are indicated are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0062] The raw material parameter characteristics involved in the following embodiments and comparative examples are as follows:

[0063] The complex phase corundum particles are sintered Al2O3-rich spinel, the main phases are 75wt%-95wt% corundum phase and 5wt%-25wt% aluminum-magnesium spinel eutectic, wherein the Al2O3 content is ≥94.0wt%, the MgO content is 1wt%-5wt%, and the Al2O3+MgO content is ≥98.5wt%. The complex phase corundum particles are firstly ball milled to obtain the corresponding particle size requirements, namely: 20-50 mass parts particle size 1: 1-0.5mm, excluding 1mm; 20-70 mass parts particle size 2: 0.5-0.15mm, excluding 0.5mm. Before being used to prepare chromium-free and carbon-free complex phase corundum drainage sand, it needs to be treated by silica sol impregnation and coating. The specific method is: immerse the complex phase corundum in the silica sol solution, and place them together in a vacuum device, vacuum treatment, the vacuum degree is below 0.1MPa, and the pressure is maintained for more than 2 hours. The SiO2 content in the silica sol solution used is 30wt% to 40wt%. The treated complex phase corundum is taken out and dried at 200℃ for 8h to obtain complex phase corundum particles treated with silica sol impregnation and coating.

[0064] The content of ZrO2 in zircon sand is ≥60.0wt%, the content of SiO2 is 25.0wt% to 40.0wt%, and the content of ZrO2+SiO2 is ≥97.0wt%.

[0065] The K2O content in potassium feldspar is 2.0wt% to 25.0wt%, the Na2O content is 2.0wt% to 20.0wt%, and the SiO2 content is ≥60.0wt%.

[0066] The Al2O3 content in andalusite is 50.0wt%~60.0wt%, the SiO2 content is 40.0wt%~50.0wt%, and the K2O+Na2O content is ≤1.0wt%.

[0067] The particle size of the silicon oxide micropowder is ≤2.0 μm, and the SiO2 content in the composition is ≥95.0wt%.

[0068] The particle size of the alumina micropowder is ≤4.0 μm, and the Al2O3 content in the composition is ≥99.0wt%.

[0069] The SiO2 content in the silica sol is 30wt% to 40wt%, the Na2O content is ≤0.7wt%, the SiO2 particle size is 5 to 25nm, and the pH value (20°C) is 8.5 to 10.5.

[0070] The Cr2O3 content in the chromite is ≥46.0wt%, the Fe2O3 content is ≤28.0wt%, and the MgO content is ≤11.0wt%.

[0071] The SiO2 content in quartz sand is ≥98.0wt%.

[0072] C in the phenolic resin is ≥35.0wt%.

[0073] C in carbon black ≥ 99.0wt%.

[0074] Embodiment 1~5:

[0075] Calculated by mass, 1 part of aluminum silicon binder (Yixing Zili Micro Powder Material Technology Co., Ltd., LIALUGEL-80 high-strength aluminum silicon binder, particle size not greater than 5μm, Al2O3+SiO2 content ≥85.00wt%, 950℃ ignition loss ≤5.0wt%), 3.0 parts of silicon oxide powder, and 4 parts of aluminum oxide powder are co-grinded in a high-energy ball mill for 2.5 hours at a speed of 150r / min to obtain an aluminum silicon modifier with a particle size not greater than 3μm.

[0076] The raw material composition of chrome-free and carbon-free composite corundum drainage sand is shown in Table 1. The composite corundum particles impregnated and coated with silica sol, zircon sand and sintering aid are mixed evenly in a mixer, and then silica sol is added and mixed evenly, and finally, aluminum silicon modifier is added and mixed evenly, and then dried and kept at 150-250℃ for 8h, the false particles after drying are removed, and the product particles are sieved to prepare chrome-free and carbon-free composite corundum drainage sand. The particle size composition, moisture, bulk density, repose angle, sintering layer thickness and high temperature compressive strength after sintering test (1650℃×2h), and ladle self-opening rate of chrome-free and carbon-free composite corundum drainage sand are tested, and the test results are shown in Table 3.

[0077] Table 1

[0078]

[0079] Comparative Examples 1 to 3:

[0080] Comparative Example 1: The raw material components of the complex phase corundum drainage sand are shown in Table 2 by mass. Complex phase corundum particles are used and the preparation method is the same as that of Example 3.

[0081] Comparative Example 2 and Comparative Example 3: The raw material components of the chromium drainage sand of Comparative Example 2 and the zirconium drainage sand of Comparative Example 3 are shown in Table 2 by mass. The chromite, zircon sand (if any), quartz sand and sintering aid are mixed evenly in a mixer, and then phenolic resin is added and mixed evenly, and finally carbon black is added and mixed evenly, and the mixture is dried and kept warm at 150-250°C for 8h, and the false particles after drying are removed, and the product particles are sieved to prepare chromium / zirconium drainage sand. The particle size composition, moisture, bulk density, repose angle, sintering layer thickness and high temperature compressive strength after sintering test (1650°C×2h), and ladle self-opening rate of the comparative drainage sand are tested, and the test results are shown in Table 3.

[0082] Table 2

[0083]

[0084] Table 3

[0085]

[0086] It can be seen that the chromium-free and carbon-free complex phase corundum drainage sand of the present invention has excellent fluidity, can quickly form a sintered layer, and has a thin sintered layer and low high-temperature compressive strength. It is suitable for the smelting of special types of steel, has a high self-opening rate of the refining ladle, reduces oxygen burning and pouring, reduces continuous casting interruptions, ensures efficient and smooth continuous casting production, and improves the quality of steel ingots.

[0087] Comparing Example 3 with Comparative Example 1, after the complex phase corundum particles are treated by silica sol impregnation and coating, the uniformity of the obtained drainage sand particles is improved, the packing density and fluidity of the product are improved (smaller angle of repose), the sintering properties of the particles and micropowders are optimized, the high temperature compressive strength and the thickness of the sintered layer are reduced, and the self-opening rate is improved.

[0088] It can be seen from Examples 1 to 5 that the chromium-free and carbon-free multiphase corundum drainage sand of the present invention can meet the requirements of molten steel smelting and grade steel smelting, and can eliminate the influence of Cr2O3 and C on the quality of molten steel.

[0089] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A chromium-free and carbon-free complex phase corundum drainage sand for steel smelting, characterized in that: The raw material composition includes, by weight: The preparation method of the complex phase corundum treated by silica sol impregnation and coating comprises: immersing the complex phase corundum raw material into a silica sol solution, and then placing it in a vacuum device for vacuum treatment, with a vacuum degree of less than 0.1 MPa, and maintaining the pressure for more than 2 hours, wherein the SiO2 content in the silica sol solution is 30wt% to 40wt%, taking out the treated complex phase corundum, and drying it at a low temperature of 150 to 250° C. to obtain the complex phase corundum treated by silica sol impregnation and coating; The sintering aid includes one or two of potassium feldspar and andalusite; The raw material mass parts of the aluminum silicon modifier include: 0.5-4 parts of alumina powder, 0.5-3 parts of silicon oxide powder, 0.5 to 1 part of aluminum silicon binder.

2. The chromium-free and carbon-free complex phase corundum drainage sand for grade steel smelting according to claim 1, characterized in that: The total mass of the complex phase corundum treated by silica sol impregnation coating, zircon sand, sintering aid, silica sol and aluminum silicon modifier is 100 parts.

3. The chromium-free and carbon-free complex phase corundum drainage sand for grade steel smelting according to claim 1, characterized in that: The proportion of particles with a particle size of 0.088 to <1.0 mm in the chromium-free and carbon-free complex phase corundum drainage sand for steel smelting is ≥90%, preferably >95%; The moisture content of the chromium-free and carbon-free complex phase corundum drainage sand for steel smelting is ≤0.3wt%, preferably ≤0.05wt%; The bulk density of the chromium-free and carbon-free complex phase corundum drainage sand for steel smelting is greater than 1.9g / cm 3 ; The repose angle of the chromium-free and carbon-free complex phase corundum drainage sand for smelting the above-mentioned steel is ≤18.5°; The self-opening rate of the chromium-free and carbon-free complex phase corundum drainage sand used for smelting the above-mentioned steel type is greater than 96%.

4. The chromium-free and carbon-free complex phase corundum drainage sand for grade steel smelting according to claim 1, characterized in that: The composite corundum raw material is one or both of fused Al2O3-rich spinel and sintered Al2O3-rich spinel, and the main phases are 75wt% to 95wt% corundum phase and 5wt% to 25wt% aluminum-magnesium spinel eutectic; The Al2O3 content in the multiphase corundum raw material is ≥94.0wt%, the MgO content is 1wt% to 5wt%, and the Al2O3+MgO content is ≥98.5wt%; In terms of mass fractions, the particle size distributions of the complex phase corundum raw material and the complex phase corundum treated by silica sol impregnation and coating are independently: 1~0.5mm, excluding 1mm 20~50 parts, 0.5~0.15mm, excluding 0.5mm 20~70 parts; In the preparation method of the multiphase corundum treated by silica sol impregnation and coating, the low temperature drying is carried out at 150 to 250° C. and the heat preservation is carried out for 5 to 12 hours.

5. The chromium-free and carbon-free complex phase corundum drainage sand for grade steel smelting according to claim 1, characterized in that: The particle size of the zircon sand is 0.5 to 0.088 mm, excluding 0.5 mm; The zircon sand has a ZrO2 content of ≥60.0wt%, a SiO2 content of 25.0wt% to 40.0wt%, and a ZrO2+SiO2 content of ≥97.0wt%.

6. The chromium-free and carbon-free complex phase corundum drainage sand for grade steel smelting according to claim 1, characterized in that: In the sintering aid, the mass ratio of the andalusite to the potassium feldspar is 1:1.5-8; The particle size of the potassium feldspar is 1.0 to 0.15 mm, excluding 1 mm; The potassium feldspar has a K2O content of 2.0wt% to 25.0wt%, a Na2O content of 2.0wt% to 20.0wt%, and a SiO2 content of ≥60.0wt%; The particle size of the andalusite is 1.0 to 0.15 mm, excluding 1 mm; The andalusite has an Al2O3 content of 50.0wt% to 60.0wt%, a SiO2 content of 40.0wt% to 50.0wt%, and a K2O+Na2O content of ≤1.0wt%.

7. The chromium-free and carbon-free complex phase corundum drainage sand for grade steel smelting according to claim 1, characterized in that: The particle size of the aluminum silicon modifier is ≤3 μm; The particle size of the alumina powder is ≤4.0 μm, and the Al2O3 content in the composition of the alumina powder is ≥99.0 wt%; The particle size of the silicon oxide micropowder is ≤2.0 μm, and the SiO2 content in the composition of the silicon oxide micropowder is ≥95.0 wt%; The particle size of the aluminum-silicon binder is not greater than 5 μm, and the content of Al2O3+SiO2 in the composition of the aluminum-silicon binder is ≥85.00wt%, and the ignition loss at 950°C is ≤5.0wt%; The preparation method of the aluminum silicon modifier comprises: grinding aluminum oxide fine powder, silicon oxide fine powder and aluminum silicon binder to obtain the aluminum silicon modifier; The co-milling is ball milling, the ball milling speed is 100-300 rpm, and the ball milling time is 2.0-3.0 h.

8. The chromium-free and carbon-free complex phase corundum drainage sand for grade steel smelting according to claim 1, characterized in that: The SiO2 content in the silica sol is 30wt% to 40wt%, the Na2O content is ≤0.7wt%, the SiO2 particle size in the silica sol is 5 to 25nm, and the pH value of the silica sol at 20°C is 8.5 to 10.

5.

9. The method for preparing chromium-free and carbon-free complex phase corundum drainage sand for grade steel smelting according to any one of claims 1 to 8, characterized in that: include: First, the complex phase corundum impregnated and coated with silica sol, zircon sand and sintering aid are mixed evenly, then the silica sol is added and mixed evenly, and then the aluminum silicon modifier is added and mixed evenly, and the mixture is dried at a low temperature of 150-250°C, false particles after drying are removed, and the product particles are sieved to obtain the chromium-free and carbon-free complex phase corundum drainage sand for smelting the said variety of steel.

10. The method for preparing chromium-free and carbon-free complex phase corundum drainage sand for grade steel smelting according to claim 9, characterized in that: In the preparation method of the chromium-free and carbon-free complex phase corundum drainage sand for smelting the steel, the sand is dried and kept warm at a low temperature of 150 to 250° C. for 5 to 12 hours.

Citation Information

Patent Citations

  • Chrome drainage sand for special steel and preparation technology thereof

    CN101972847B

  • Manufacturing method of low-chromium environment-friendly ladle filler sand

    CN102000790A

  • A kind of chrome-magnesium-zirconium drainage sand and its preparation method

    CN103708842B

  • A kind of preparation method of refined chrome drainage sand

    CN104148625B

  • A tabular corundum-based diversion sand and its preparation method

    CN104193353B

Cited By

  • Determination method for highest transfer temperature of molten steel for avoiding oxygen burning casting of steel ladle caused by excessive sintering of stuffing sand

    CN120828129A

  • A method for determining the maximum transfer temperature of molten steel to avoid excessive sintering of the sand caused by ladle oxygen burning and pouring

    CN120828129B